Institutional analysis and capacity building of African agricultural carbon projects case study. Kenya smallholder agriculture carbon finance project: Vi agroforestry - Shames, Seth; Wekesa, Amos; Wachiye, E. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
Case study for the report "Institutional innovations in African smallholder carbon projects" available at http://hdl.handle.net/10568/21222